Rancang Bangun Sistem Kamera Pengawas Berbasis J2me - Pradiptya, Rampa; Sutanto, Teguh; Purnama, Rangsang (Jurnal JSIKA, 2012)
The desire of every person to have a sense of security against the property owned is one purpose built monitoring systems. Many systems that have been applied for monitoring in specific areas such example is CCTV. However, the existing security system can not be monitored by the owner / user, so sometimes having trouble to check. The growth of telecommunications and information technology provides several advantages. Mobile phones are one of telecommunication products. Nowadays mobile phones can not only be used to conduct the telephone, but also for the use of communication technologies by utilizing the Internet as supporters. The use of Internet technology is also impacting on the development of software and hardware as well as open up opportunities for us to develop applications and systems to facilitate various activities. the variety of information we were able to use the software and hardware that we make for specific purposes, including CCTV building applications using J2ME technology on mobile devices.     Keyword : Closed-Circuit Television (CCTV), J2ME, Webservice.